Analysis of Factors Causing CO2 Emissions in Developed, Developing, and BRICS Countries - Jati, Endang Laras; Kuncoro, Trian Gigih (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
As time goes by, technological facilities are experiencing rapid progress; this can encourage the growth of the industrial and transportation sectors, which can increase consumption of fuels, especially fossil fuels. The more humans use fossil fuels, the more CO2 emissions in the world will increase. Co2 emissions are believed to trigger climate change and global warming. In this study, time series and cross-section techniques are used to collect secondary data utilizing quantitative approaches. This research examines the level of CO2 emissions in developed countries, developing countries, and BRICS countries in 2013–2022. The research results show several things, namely (1) forest areas do not have a substantial impact on CO2 emissions in developed, developing, and BRICS countries. (2) The use of renewable energy has not completely reduced the problem of CO2 emissions because there remain a number of nations that have not optimized renewable energy. (3) Fossil energy consumption is not significant in CO2 emissions in several developed countries and BRICS countries because most countries are starting to implement low-carbon energy so they can reduce CO2 emissions. (4) The use of technology is not significant for developed countries and BRICS because they have implemented advanced efficiency technology that is environmentally friendly. (5) Economic growth has a major impact on CO2 emissions in BRICS, developing, and industrialized nations since the larger the income per capita, the greater the use of technology that uses fossil fuels.